Optical coherence tomography angiography of the foveal avascular zone in diabetic retinopathy - Freiberg, Florentina Joyce; Pfau, Maximilian; Wons, Juliana; Wirth, Magdalena A.; Becker, Matthias D.; Michels, Stephan (Graefe's archive for clinical and experimental ophthalmology, 2016)
To analyze foveal avascular zone (FAZ) dimensions and symmetry in patients with diabetic retinopathy (DR) compared to healthy controls using optical coherence tomography angiography (OCT angiography).